Amplified Detection of a Unique Genomic Viral Marker Using Fluorescently Labeled Liposomes. Issue 11 (15th March 2018) - AbouShaheen, Samir; Fakih, Hassan H.; Kobeissi, Jana M.; Karam, Pierre
Abstract: Sensitive and enzyme‐free detection of specific oligonucleotide sequences is a pressing need in the field of precision and personalized medicine. In this work the detection of a unique genetic marker for hepatitis B virus with a low detection limit of 5 × 10 −12 m and a fast assay time is reported. In the assay presented here, fluorescently labeled liposomes are captured by gold‐decorated polystyrene beads using the target sequence as the building block. This is achieved by modifying the microbeads and the liposomes each with half of the complementary sequence. After a short incubation time with the target of interest, the fluorescent signal of the bridged bead–liposome assembly is detected via flow cytometry. Each liposome is labeled with ≈48 lipid soluble dyes resulting in an amplified fluorescent signal for every sensing event. The detection of the viral marker is even possible in an artificial serum‐spiked sample. Abstract : An ultrasensitive strategy for the detection of hepatitis B virus unique gene sequence is developed based on gold‐coated polystyrene beads and fluorescently labeled liposomes. The assay is fast and simple and could be easily adapted to detect other viral sequences of interest. Its ability to detect targets in complex matrices makes it a promising platform for rapid diagnosis.